Dissemination of multiple drug resistance genes by class 1 integrons in klebsiella pneumoniae isolates from four countries: a comparative study (2011)
A comparative genetic analysis of 42 clinical Klebsiella pneumoniae isolates, resistant to two or more antibiotics belonging to the broad-spectrum β-lactam group, sourced from Sydney, Australia, and three South American countries is presented. The study focuses on the genetic contexts of class 1 integrons, mobilizable genetic elements best known for their role in the rapid evolution of antibiotic resistance among Gram-negative pathogens. It was found that the class 1 integrons in this cohort were located in a number of different genetic contexts with clear regional differences. In Sydney, IS26-associated Tn21-like transposons on IncL/M plasmids contribute greatly to the dispersal of integron-associated multiple-drug-resistant (MDR) loci. In contrast, in the South American countries, Tn1696-like transposons on an IncA/C plasmid(s) appeared to be disseminating a characteristic MDR region. A range of mobile genetic elements is clearly being recruited by clinically important mobile class 1 integrons, and these elements appear to be becoming more common with time. This in turn is driving the evolution of complex and laterally mobile MDR units and may further complicate antibiotic therapy.